TRAINING NEEDS PERCEIVED BY TRIBAL FARMERS IN BACKYARD PIGGERY FARMING IN ASSAM - SHARAD AVHAD4, JANMONI SHYAM1 ; HEMA TRIPATHI2 ; JYOTI (Indian Journal of Animal Production and Management, 2017)
An ex-post facto study was conducted in Dhemaji and Karbi Anglong districts of Assam state with the objective to understand the extent of training needs perceived by tribal farmers in backyard piggery farming. Data were collected personally from 200 tribal families practising backyard piggery from twenty different villages through interview schedule. The study revealed that selection of animals (88.00 %), feeding schedule of pregnant animals (83.50 %), knowledge about common diseases (78.50 %), care of pregnant animals (81.00 %), and knowledge about credit facilities (65.50 %) were the most important areas for training needs perceived by the farmers. The average total weighted mean score of the different sub areas of training needs depicted that breeding and feeding were the most important areas of training needs perceived by the respondents followed by health care, marketing and management. About 60.00 per cent of the tribal respondents had medium level of overall training needs in backyard piggery farming. Positive and significant correlation was found between age, education, land holding, experience in pig rearing, herd size and annual income with their training needs. Key words : Training needs, tribal farmers, backyard piggery farming.